Nasal profile differences between skeletal Class II and Class III in Malay females - Ibrahim, Sara; Cheong, Joo Ming; Md Dasor, Maryati; Ahmad Alwi, Akmal Azim; Mohd Ibrahim, Mohamad Shafiq (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2024)
PURPOSE: To compare the nasal profile differences between skeletal Class II and Class III Malay females. METHODS: 30 pre-treatment lateral cephalograms of skeletal Class II and Class III female patients, aged 20-30 years old, were retrieved from IIUM Postgraduate Orthodontics Clinic. After calibration, the cephalograms were manually hand traced using a 0.05mm lead pencil on an acetate sheet on a light viewing box in a dark room. Five nasal parameters (nasomental, nasofrontal, nasofacial, nasolabial, and nasal bone angle) were measured using a protractor and metal ruler. The measurements were repeated after two weeks for intra-examiner reliability with intraclass correlation coefficient (ICC). Independent t-test was used to measure the differences between the groups. RESULTS: The study found that the nasofrontal, nasofacial and nasolabial angles were significantly more obtuse in the skeletal Class II group (139.63±5.44º; 32.17±3.25º; 94.03±12.07º) compared to the skeletal Class III group (136.40±6.91º; 28.47±3.31º; 82.60±13.32º), with mean differences of 3.23º (p=0.049), 3.70º (p<0.001) and 11.43 º (p<0.001) respectively. Additionally, the nasomental angle was found to be larger in the skeletal Class III group (140.07±4.26º) as compared to the skeletal Class II group (129.83±5.59º), with a mean difference of 10.23º (p<0.001). However, no significant differences were found in the nasal bone angles between the groups. CONCLUSION: The nose of skeletal Class II patients appears longer and more projected from the face as compared to skeletal Class III patients.